Наукові і технологічні основи виробництва високоефективних видів сортового та бунтового прокату - Парусов, Е.В.; Левченко, Г.В.; Луценко, В.А.; Бобирь, С.В.; Парусов, О.В.; Чуйко, І.М.; Голубенко, Т.М. (Physico-technological Institute of Metals and Alloys, 2023)
The history of the foundation, development and the main scientific areas of activity of the department of heat treatment of metal for mechanical engineering of the Iron and Steel Institute of Z.I. Nekrasov of the NAS of Ukraine are presented. It is shown, that the department specialists made a significant contribution to the development of the scientific foundations for the creation of technological processes for the production of high-quality rolled metal of a wide brand composition and for various purposes. The results of basic research are used in the development and improvement of the technology for the production of hot-rolled construction steel and wire rod, which are characterized by the increased consumer properties, scale and effectiveness. The scientific developments based on further development of ideas about modern materials science have found their practical implementation at many metallurgical, hardware and machine-building enterprises. The industrially introduced innovative modes of deformation-heat and heat treatment of steels from both rolling and individual heating, including using cryogenic treatment, led to an increase in their strength class, durability, wear and heat resistance during operation. The methods of ultrasonic testing and differential magnetic analysis of alloy steels were developed; author's methods are proposed for calculating the phase composition and temperatures of phase-structural transformations in alloyed and carbon steels; computer program were created for constructing isothermal and thermokinetic diagrams of the decomposition of metastable austenite, modeling the conditions of a real production process with the ability to predict the structure and mechanical properties of rolled products for various purposes depending on the chemical composition of steel and process parameters. The implemented technological solutions correspond to the level of the best world analogues, and the results of basic research have made a significant contribution to improving the energy and resource saving of the metallurgical, hardware and machine-building industries of Ukraine.